Short-term changes in 10-km race pace aerobic demand and gait mechanics following a bout of high-intensity distance running - Morgan, D. W.; Strohmeyer, H. S.; Daniels, J. T.; Beaudoin, C. C.; Craib, M. W.; Borden, R. A.; Greer, P. J.; Burleson, C. L. (European Journal of Applied Physiology, 1996)
Following treadmill accommodation and a 3-day period of tapered running, ten well-trained male distance runners [x maximum oxygen uptake (VO2max) = 71.3 ml.kg-1.min-1] performed two 10-min level treadmill runs designed to assess running economy at 90% VO2max. Video recordings were obtained during the last minute of each run to quantify selected gait descriptors. Two to 3 days following the second economy run, each subject completed 30 min of high-intensity (HI) running at 90% VO2max. One 2, and 4 days after the HI run, subjects repeated the 10-min economy runs. Compared to pre HI-run values, no significant change (P > 0.05) in running economy was observed during the post-HI runs. Biomechanical analyses also revealed that running style remained unaltered after the HI run. These results support earlier findings obtained on moderately trained subjects featuring measurement of running economy and gait mechanics at less-demanding intensities and suggest that among well-trained athletes, 30 min of HI running does not elicit an increase in VO2 or disrupt gait mechanics over the short term in subsequent distance runs performed at near-maximal speeds.